Penguatan Kompetensi Gastronomi Berbasis Bahan Pangan Lokal melalui Workshop dan Cooking Class bagi Masyarakat di Denpasar, Bali - Ni Luh Gde Sari Dewi Astuti; Putu Eka Wirawan; I Gusti Ayu Eka Suwintari; Anak Agung Istri Putera Widiastiti; Putu Renita Amelia Putri; I Kadek Rama Putra Satria (Civiliza Publishing, 2026)
This community service program is motivated by the limited gastronomic competencies of local communities in Denpasar, Bali, in utilizing local food resources innovatively while maintaining cultural value and economic competitiveness. Although Bali possesses rich culinary heritage and abundant local ingredients, their transformation into value-added gastronomic products remains suboptimal, particularly in terms of production skills, business management, and marketing strategies. The purpose of this program is to strengthen community capacity through an integrated approach involving gastronomic training, business management development, marketing enhancement, and cultural preservation. The methods applied include participatory workshops, hands-on cooking classes, business mentoring, and interactive educational sessions, supported by observation, discussion, and evaluation processes. The results indicate a significant improvement in participants’ knowledge and technical skills in processing local food ingredients into innovative and aesthetically appealing culinary products. In addition, participants demonstrated enhanced understanding of basic business management, including cost control, financial recording, and simple business planning, as well as improved ability to promote products using storytelling and digital media. The program also contributed to increasing community awareness of preserving local culinary heritage as part of cultural identity. In conclusion, the integrated approach combining gastronomic training, entrepreneurship development, and cultural education proves effective in strengthening community capacity, enhancing the economic value of local food, and supporting sustainable cultural preservation. This model has the potential to be replicated in other regions with similar local resource potential.